Nilai Gizi dan Organoleptik Bakso Daging Ayam Yang Ditambahkan Tepung Kacang Koro Pedang (Canavalia gladianta) - Ni Made Andry Kartika; Alimuddin Alimuddin (LPPM Universitas Mataram, 2020)
Meetball is a common food in society and has good nutritional volue. Sword koro can be used as a binder besides having better quality and protein than tapioca flour. This study aims to determine the effect koro pedang flour to the nutritional value and organoleptic value f chicken meatballs. The method used in the study was a completely randomized designconsisting of 5 teatments and repeated 5 times, namely: KO (control), K1 (chicken meatballs + koro pedang flour 20%), K2 (chicken meatballs + koro pedang flour 25%), K3 (chicken meatballs + koro pedang flour 30%) and K4 (chicken meatballs + + koro pedang flour 35%). The variables measured ware the nutritional value or chemical composition (moisture content, ash content, fat content, and crure protein), and the organoleptic value of chicken meatballs with the addition of koro pedang flour (Canavalia Gladiante). Analysis of the data used the analysis of variance based on completely randomized design CRD), from the results of different analyzes followed by the LSD test. The results showed that the nutritional value showed very significant results or all treatments (K1,K2,K3 dan K4) were significantly different(P>0.01) for crude protein, crude fiber, crude fat and ash. Maenwhile, for the water content in this treatment, no significant results were found. The highest average value is shown in the K4 tretment for protein, crude fat, crude fiber and ash. The organoleptic value showed significant results (P<0.05) on the K1 treatment for taste, color, texture and acceptance. Maenwhile, the aroma is insignificant because the aroma of the meatballs added with koro flour has a very strong and distinctive aroma